Thoracic kyphosis and rate of incident vertebral fractures: the Fracture Intervention Trial. Issue 3 (March 2016) - Katzman, W.; Vittinghoff, E.; Kado, D.; Lane, N.; Ensrud, K.; Shipp, K.
Abstract Summary Biomechanical analyses support the theory that thoracic spine hyperkyphosis may increase risk of new vertebral fractures. While greater kyphosis was associated with an increased rate of incident vertebral fractures, our analysis does not show an independent association of kyphosis on incident fracture, after adjustment for prevalent vertebral fracture. Excessive kyphosis may still be a clinical marker for prevalent vertebral fracture. Introduction Biomechanical analyses suggest hyperkyphosis may increase risk of incident vertebral fracture by increasing the load on vertebral bodies during daily activities. We propose to assess the association of kyphosis with incident radiographic vertebral fracture. Methods We used data from the Fracture Intervention Trial among 3038 women 55–81 years of age with low bone mineral density (BMD). Baseline kyphosis angle was measured using a Debrunner kyphometer. Vertebral fractures were assessed at baseline and follow-up from lateral radiographs of the thoracic and lumbar spine. We used Poisson models to estimate the independent association of kyphosis with incident fracture, controlling for age and femoral neck BMD. Results Mean baseline kyphosis was 48° (SD = 12) (range 7–83). At baseline, 962 (32 %) participants had a prevalent fracture. There were 221 incident fractures over a median of 4 years. At baseline, prevalent fracture was associated with 3.7° greater average kyphosis (95 % CI 2.8–4.6, p < 0.0005), adjusting for age and femoral neck BMD. Before adjusting for prevalent fracture, each 10° greater kyphosis was associated with 22 % increase (95 % CI 8–38 %, p = 0.001) in annualized rate of new radiographic vertebral fracture, adjusting for age and femoral neck BMD. After additional adjustment for prevalent fracture, estimated increased annualized rate was attenuated and no longer significant, 8 % per 10° kyphosis (95 % CI −4 to 22 %, p = 0.18). Conclusions While greater kyphosis increased the rate of incident vertebral fractures, our analysis does not show an independent association of kyphosis on incident fracture, after adjustment for prevalent vertebral fracture. Excessive kyphosis may still be a clinical marker for prevalent vertebral fracture.